Stress Management strategies in the traditions of Prophet (ﷺ) and stories of other Prophets (علیہ السلام) - Hashmi, Asma; Zaman, Nazia (MEI, 2023)
Stress is a situation which is the fact of life for every human being, and so this situation cannot be ignored instead everyone have to face it and deal with it. It is a psychological and mental phenomenon related to mind. It is a complicated phenomenon that depends on moods, circumstances of surroundings, occurrences and conditions in which human being spend their life. As stress is a kind of mental illness so there are natural, religious and medical techniques to treat and diminish it. All religions of world regardless of any discrimination preach tranquility of mind and positive thought. Similarly, Islām as a guide in all areas of life , provides Muslims a system of actions, moral values , and social ethics that assists them in making adjustable and flexible stress management strategies to fight with stressful life happenings. Hence present research discuss strategies of managing stress present in Islām . In this way Prophetic traditions and techniques used by past prophets and companions from existing literature on stress management and Islām are discussed in detail. The research is analytical in nature and employs qualitative method for the collection of data. Content analysis has been utilized. In addition, historical method has also been used. This research concluded that Islām gives solutions and strategies for management of stress , anxiety, depression and such mental illnesses in the form of strategies in Prophetic traditions and techniques used by past prophets and companions. Key words: Stress, Islam, Management, Strategies, Prophetic Tradition, Prophets.